Digitalization of Regional Economy as a Public Administration Approach in Stimulating Socio-Economic Development Regional of Ukraine - Kovalenko, Mykola; Sobol, Roman; Vanina, Yana; Berlizova, Viktoriia; SobolMariіa (Theory and Practice of Public Administration, 2024)
The relevance of this study is determined by the need to form effective regional policy capable of ensuring balanced socio-economic development of the regions of Ukraine based on innovative-investment reproduction in the context of the fourth industrial revolution, increasing competition between territories, political instability, and social tension, as well as growing external and internal economic, social, military, environmental, and other threats and challenges. A primary factor in the substantive content of public administration of regional development is the change in the goal-setting of territorial development and the principles of distributing economic resources among regions. State regional policy of Ukraine should be aimed at improving the quality of life of the population, careful use of all regional resources, improving the structure of material production, and environmental improvement, stimulating innovation, and implementing new technologies. This system of guidelines implies the activation of the process of digitalization of the regional economy, which is based on the use of advanced innovative technologies permeating all stages of business processes, achievements of traditional science-intensive and intellectual sectors, as well as the modern experience of regional companies actively implementing innovative products and services. The transition of primary and supporting business processes to the digital space, training personnel in digital skills for working in the Internet information and telecommunication network, and shifting the labor process from material-technical factors to human ones are initial conditions for the successful digital transformation of the regional economy. For Ukraine, there is an increasing need to develop the national economy by creating state enterprises that will effectively operate in both domestic and external markets. Such economic entities should become “locomotives” and “growth points” of the national economy, generating impulses and creating a multiplier effect to increase the economic activity of the private sector, development of high-tech industries, innovations, and more. This approach is closely linked to the state regional policy aimed at balanced regional development, particularly through supporting key enterprises that can become the foundation for economic growth in the regions. An important aspect of this policy is ensuring equal opportunities for regional development and reducing disparities between them. The processes of digital transformation open up new opportunities for the development of both state and private enterprises, which can contribute to the activation of economic activity in the regions. In particular, digitalization allows for the optimization of management processes, easier access to markets and resources, as well as fostering innovation. Priority areas for regulating digital transformation of the regional economy by the state should include ensuring consumer rights, organizing a set of cybersecurity measures, and promoting online trade. These areas play a key role in developing business opportunities for representatives of the regional business community and protecting public interests, acting as multipliers to enhance economic activity and investment appeal of the regions. The use of digital platforms can provide numerous advantages, including: stimulating innovation adoption, increasing productivity, creating new consumer values, expanding market opportunities, reducing transaction costs, improving communication, and enhancing overall well-being and quality of life. At the regional level, this can contribute to optimizing resource management, developing local economies, enhancing regional competitiveness, and ensuring more effective implementation of state programs and initiatives. It is shown that the application of a digital ecosystem is of particular importance for public administration, as it allows for the creation of various incentives to support socio-economic development of the region. To attract participants to the digital ecosystem, appropriate incentives need to be developed. Such participation can not only contribute to financial results growth but also strengthen competitive advantages, enhance brand positions and organizational reputation, and improve resilience, productivity, and effectiveness, providing other non-financial benefits. Interaction with various digital platforms expands the boundaries of enterprises and operations of organizations, encouraging them to seek and utilize new opportunities beyond traditional areas of activity. This forms a new level of creating and providing value to consumers and improves the efficiency of local self-government bodies. Consumer participation in the regional digital ecosystem allows not only saving money and time on acquiring necessary goods and services without intermediaries but also gaining new knowledge and competencies, enhancing status and self-esteem. It also contributes to a sense of social significance and belonging to the global network of interactions between people, organizations, and public authorities. Measures for organizing the conversion of digital business platforms into a unified regional digital ecosystem have been developed. The experience of China regarding the development of regional digital ecosystems is extremely valuable for Ukraine, as it illustrates effective strategies for integrating innovations and technologies aimed at increasing the resilience and competitiveness of regions. It also highlights the need for systemic reforms in organizing the economic system and state economic regulation. Such reforms are key to ensuring socio-economic development and for the successful adaptation and development of digital initiatives in Ukrainian regions.